(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In accordance with the purpose and objectives of this study, we studied the course of pregnancy and childbirth in 200 women at a gestational age of 22-36 weeks. The main group consisted of 65 women with a threatened miscarriage, 40 women with preterm labor without amniotic fluid and 45 women with amniotic fluid, the control group consisted of 50 women with a physiological course of pregnancy. Immunological studies were carried out in the immunological laboratory of the Specialized Research Republican Center for Obstetrics and Gynecology.